Transcatheter arterial embolization followed by laparoscopic anatomic hepatectomy for spontaneous rupture of a giant hepatic angiomyolipoma: a case report - Wang, Jianjun; Shi, Ruizi; Luo, Hua; Yang, Pei; Luo, Huiwen; Gao, Ziqing; Wang, Decai; Zeng, Xintao (Frontiers in Surgery, 2023)
Hepatic angiomyolipoma is a rare and possibly cancerous mesenchymal tumor that consists of three components: blood vessels, smooth muscle cells, and adipose tissue. In this paper, we reported a case of a 36-year-old man who had a giant hepatic angiomyolipoma with spontaneous rupture and hemorrhage. The patient was admitted to our hospital with sudden upper abdominal pain for 3 hours. A giant tumor was found in the left and caudate lobes of the liver, as well as significant blood collection around the liver and in the pelvis. Hemoglobin, liver function test results, and serum tumor maker levels were all within normal ranges. To prevent bleeding, emergency angiography and embolization were performed. During angiography, it was discovered that the tumor was supplied by the left hepatic artery and had a very rich internal blood supply. A massive left hepatic mass of about 11 cm in diameter was found bulging from the surface of the liver and rupturing there during laparoscopic exploration a week later. The rupture was strongly adhered to the smaller curvature of the stomach. The patient underwent laparoscopic left hemihepatectomy and caudate lobectomy, and the tumor specimen was brown, with clear boundaries with the surrounding normal liver parenchyma, and there were a large number of necrotic lesions inside the tumor. Histopathological results confirmed the mass as hepatic angiomyolipoma with negative resection margins. Immunohistochemical staining indicated that the tumor had positive homatropine methylbromide-45. After 13 months of follow-up, no tumor recurrence or metastasis occurred in the patient.